2021
DOI: 10.22146/ijp.1365
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with personal protective equipment use among non-medical healthcare professionals during Covid-19 pandemic

Abstract: Non-medical healthcare professionals, including pharmacists, pharmacy technicians, nutritionists, and radiographers, have a high risk of  COVID-19 infection during work. Personal protective equipment use has shown effective in preventing virus transmission. This study aimed to investigate the compliance with personal protective equipment use and identify the factors that may influence their compliance. The study was designed cross-sectionally, with a self-administered questionnaire. The respondents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…Surprisingly, among all participants, those who worked for longer periods (more than a year) used less suitable PPE than those with less experience, which is the opposite of our assumption nor the literature that ones with more work dura-literature that ones with more work dura-that ones with more work duration and experience had more protective behaviours and better compliance with PPE than another group [21,23],but correlated with another paper that HCW with more experience abided the protective measures lower than those with less experience [24]. We assume that the participants with more working experience maybe negligent and thought that their methods of using PPE were already appropriate without awareness of the current guideline.…”
Section: Discussioncontrasting
confidence: 80%
“…Surprisingly, among all participants, those who worked for longer periods (more than a year) used less suitable PPE than those with less experience, which is the opposite of our assumption nor the literature that ones with more work dura-literature that ones with more work dura-that ones with more work duration and experience had more protective behaviours and better compliance with PPE than another group [21,23],but correlated with another paper that HCW with more experience abided the protective measures lower than those with less experience [24]. We assume that the participants with more working experience maybe negligent and thought that their methods of using PPE were already appropriate without awareness of the current guideline.…”
Section: Discussioncontrasting
confidence: 80%
“…The environmental-organizational factors in the study reveal the availability of supporting facilities plays an important role in supporting community pharmacists' compliance. In addition, a previous study in Malang Indonesia reported that lack of punishment does not affected to compliance level of pharmacists (24). This finding is in line that one of the factors that influence behaviour at work is enabling factors, one of them is facilities or infrastructure that support the occurrence of behaviour by someone (25).…”
Section: Discussionsupporting
confidence: 67%
“…The lowest compliance item was “wearing N95 respirator” among those who had provided direct care to confirmed COVID-19 patients (85.1%) or performed AGP (79.6%). Previous studies have reported shortages of PPE and lack of training as the major reasons for non-compliance ( [44] , [45] , [46] , [47] , [48] ), and different countries have reported a wide range of compliance rates (32.0-96.5%) ( [44] , [45] , [46] , [47] , [48] , [49] ). Comparatively, the compliance rates found in our study was fairly high.…”
Section: Resultsmentioning
confidence: 99%